PENGARUH LEVERAGE DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT (Studi Empiris Pada BUMN Periode 2016-2020) - Andi Diana Putri; Surifah Surifah (Magister Manajemen STIE Bank BPD Jateng, 2023)
Abstract : This study aims to analyze the effect of leverage and good corporate governance on the disclosure of sustainability reports. The research sample used was state-owned enterprises, for the 2016-2020 period. The number of samples in this study was 77. Purposive sampling technique was used in the sampling of this study. The data analysis technique used multiple linear regression test. The dependent variable in this study is the disclosure of sustainability reports which are measured based on the Global Reporting Initiative Standards guidelines issued by the Global Sustainability Standards Board (GSSB). The independent variable used is leverage and good corporate governance. This study uses a control variable, namely size. The results showed that: (1) Debt to Asset Ratio had a negative effect on the disclosure of the sustainability report. (2) Debt to Equity Ratio and the number of commissioners, and size have no effect on the disclosure of the sustainability report. (4) the proportion of independent commissioners and the number of audit committees have a positive effect on the disclosure of the sustainability report